Interrelations of Thrombo-Embolic Diseases and Blood-Group Distribution - Dick, W; Schneider, W; Brockmüller, K; Mayer, W (Thrombosis and Haemostasis, 1963)
A comparison between the repartition of the blood groups in 461 patients suffering from thromboembolic disorders and the normal distribution has shown a statistically ascertained predominance of the group A1. On the other hand the blood groups 0 and A2 are distinctly less frequent than in the normal distribution.